Claiming the city: Muslim faith-based activism as ‘lived citizenship’ in Georgia - Darieva, Tsypylma (Religion, state & society, 2023)
This contribution draws attention to faith-based activism as ‘lived citizenship’ among Georgian Muslims in Georgia. A controversial case of the construction of a mosque in multi-religious Batumi is not an isolated episode confined to the city, but goes back to a much longer dispute over Georgianness among Georgian Muslims and should be located in a wider, global perspective. An emerging regional metropolis in Georgia offers fruitful arenas for the study of the dynamics of religious activism in those domains where religion is viewed as a new source of national heritage, and where legal frameworks (i.e. laws on religious freedom) for minorities and their participation are not yet elaborated, or are constantly being negotiated and contested. This anthropologically informed study demonstrates the increasing visibility of the voices of religious minority groups and the growth of public expression of Muslim life in Georgia. It reflects this minority group’s expectation of achieving a mutual ‘sense of belonging’, and their tactics of lived citizenship and of participation in contemporary Georgia.